Haplodeficiency of Ataxia Telangiectasia Mutated Accelerates Heart Failure After Myocardial Infarction. Issue 7 (19th July 2017) - Jia, Lixin; Zhang, Wenmei; Ma, Youcai; Chen, Boya; Liu, Yan; Piao, Chunmei; Wang, Yuan; Yang, Min; Liu, Tingting; Zhang, Junmeng; Li, Taotao; Nie, Shaoping; et al.
Abstract : Background: Cell senescence is involved in the process of organ damage and repair; however, the underlying molecular mechanism needs to be further explored. Methods and Results: Senescence‐related genes (ie, p21, p53, and ataxia telangiectasia mutated [ATM]) were shown to be elevated after myocardial infarction (MI) in both mouse and human hearts. Ten‐ to 12‐week‐old male wild‐type littermates (ATM +/+ ) and ATM heterozygous mice (ATM +/− ) were subjected to MI. Cardiac echography showed that ATM haplodeficiency did not affect the survival rate but aggravated heart failure at day 28 post MI. Histologic analysis showed increased fibrosis in the noninfarct area of ATM +/− mice compared with that in ATM +/+ mice. Senescence‐associated β‐galactosidase staining showed that the number of senescent fibroblasts was decreased when ATM was haplodeficient both in vivo and in vitro. Costaining of α‐smooth muscle actin with p53 or p19 showed fewer senescent myofibroblasts in ATM +/− mouse hearts. Moreover, angiogenesis was also examined using the endothelial markers CD31 both at early (day 7) and late stages (day 28) after MI, and ATM haplodeficiency reduced angiogenesis after MI. Finally, cardiac fibroblasts were isolated from infarcted mouse heart and the medium were tested for its capacity of endothelial tubing formation, revealing that ATM haplodeficiency led to lower vascular endothelial growth factor production from cardiac fibroblast and reduced capacity of endothelial tube formation in vitro. Conclusions: The present study shows that ATM haplodeficiency decreases fibroblast senescence and vascular endothelial growth factor production and impaired angiogenesis in response to MI, leading to accelerated heart failure.